Review of Equity Crowdfunding Practices through Santara.id in the Perspective of Islamic Economic Law - Rahma Octaviani; Pas Ingrid Pamesti; Bagas Heradhyaksa (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This article aims to find out the mechanism of equity crowdfunding through the santara platform from Islamic economic law. This article uses a qualitative method using library data. This article finds that santara.id is an intermediary between investors and issuers in developing a business. The scheme is similar to the muḍārabah contract, the investor is identical to ṣāḥib al-māl, and the issuer is identical to the muḍārib. However, this activity cannot be considered as muḍārabah cooperation because there has been no concrete agreement regarding the muḍārabah agreement. This article provides suggestions so that santara.id can further develop the platform's promotion in the community. It is because santara.id can provide investment services for the middle class, both as investors and issuers.